2018
DOI: 10.3389/fnsyn.2018.00018
|View full text |Cite
|
Sign up to set email alerts
|

The Intersection of Central Dopamine System and Stroke: Potential Avenues Aiming at Enhancement of Motor Recovery

Abstract: Dopamine, a major neurotransmitter, plays a role in a wide range of brain sensorimotor functions. Parkinson's disease and schizophrenia are two major human neuropsychiatric disorders typically associated with dysfunctional dopamine activity levels, which can be alleviated through the druggability of the dopaminergic systems. Meanwhile, several studies suggest that optimal brain dopamine activity levels are also significantly impacted in other serious neurological conditions, notably stroke, but this has yet to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 291 publications
(465 reference statements)
1
30
0
Order By: Relevance
“…In recent years, a growing number of studies have indicated the involvement of dopaminergic systems in stroke modulation (Gower and Tiberi, 2018). The results of microdialysis of the present study demonstrated that cerebral ischemia induced a robust and transient release of DA extracellularly in the striatum, which is consistent with previous studies (Globus et al, 1988;Tsukada et al, 2004;Li et al, 2010;Yoshimoto et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In recent years, a growing number of studies have indicated the involvement of dopaminergic systems in stroke modulation (Gower and Tiberi, 2018). The results of microdialysis of the present study demonstrated that cerebral ischemia induced a robust and transient release of DA extracellularly in the striatum, which is consistent with previous studies (Globus et al, 1988;Tsukada et al, 2004;Li et al, 2010;Yoshimoto et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…The CPu is the structure responsible for a wide variety of behavioral functions and is highly vulnerable to ischemia (Globus et al, 1988;Alexander et al, 1990;Sabogal et al, 2014). Lesions in the striatum and transient global ischemia cause significant loss of dopaminergic substantia nigra neurons (Ichitani et al, 1991;Burke et al, 1992;Gower and Tiberi, 2018). In addition, striatal infarction downregulates TH immunoreactivity following ischemia (Yamada et al, 1996;Li et al, 2016;Mao et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Lack of response to modafinil in our study may have been the result of a mechanism of action separate from dopamine neurotransmission. Pre-clinical and clinical data suggest dopamine activity is disturbed following acute stroke, and dopamine supplementation or augmentation may be of benefit, but this requires confirmation [13,35].…”
Section: Discussionmentioning
confidence: 99%
“…Modafinil's effects appear independent of serotonin, dopamine, GABA, adenosine, histamine-3, melatonin, and benzodiazepine receptors. Compared to conventional neurostimulants, modafinil appears to be devoid of dopaminergic effects, which may be of significance as post-stroke dopaminergic system dysfunction has been recently described [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Strategies aimed at inducing brain plasticity and modulating brain activity in order to achieve functional goals are essential as well. Despite post-stroke cures and cares made great strides, there is no clear evidence on the role of pharmacological treatment in post-stroke recovery [6][7][8][9][10][11][12]. Drugs specifically aimed at acting onto neuroplasticity-based recovery mechanisms may indeed have a significant role in this field.…”
Section: Introductionmentioning
confidence: 99%